2010
DOI: 10.1002/anie.201002776
|View full text |Cite
|
Sign up to set email alerts
|

Subcomponent Assembly and Transmetalation of Dinuclear Helicates

Abstract: Metallosupramolecular self-assembly strategies and principles have been thoroughly investigated in the past 20 years with the aim of mimicking natures ability to assemble impressive supramolecular structures.[1] Despite the remarkable metal selectivity and recognition in self-assembly reactions, directed metal exchange (i.e. transmetalation) in such supramolecular structures is still underdeveloped, [2] which is surprising as transmetalation is the missing link between the currently known self-assembly strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…[5] These materials have exhibited high luminescence efficiencies, [6] stimuliresponsive behavior, [7] and self-healing properties, [8] and have been used to construct molecular electronics devices. [13] Polymer growth is favored by the strong mutual reinforcement between these two linkages,w hich allows the self-assembly of functional and persistent structures. [13] Polymer growth is favored by the strong mutual reinforcement between these two linkages,w hich allows the self-assembly of functional and persistent structures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5] These materials have exhibited high luminescence efficiencies, [6] stimuliresponsive behavior, [7] and self-healing properties, [8] and have been used to construct molecular electronics devices. [13] Polymer growth is favored by the strong mutual reinforcement between these two linkages,w hich allows the self-assembly of functional and persistent structures. [13] Polymer growth is favored by the strong mutual reinforcement between these two linkages,w hich allows the self-assembly of functional and persistent structures.…”
mentioning
confidence: 99%
“…[1e, 9] Recently,others [7a,10] and our group [11] have demonstrated that metallopolymers can be generated through subcomponent self-assembly,w herein amine and aldehyde subcomponents condense around metal ions to form dynamic covalent [12] C=Na nd coordinative N!Metal bonds simultaneously. [13] Polymer growth is favored by the strong mutual reinforcement between these two linkages,w hich allows the self-assembly of functional and persistent structures. [7a] The resulting metallopolymers can exhibit reversible stimuliresponsive behavior and they have been incorporated into various devices; [7a,11b,c,14] however,control over the length and polymerization process of these materials is yet to be demonstrated.…”
mentioning
confidence: 99%
“…Subcomponent self-assembly,i nw hich aldehyde and amine subcomponents come together around metal-ion templates,h as been used to generate complex structures in am odular and hence tunable fashion by other research groups [19] and ourselves. [20] Examples of such structures have been shown to be water-a nd buffer-stable.…”
mentioning
confidence: 99%
“…5), halting the anti ligands' rapid rotation. Although transmetallation has been demonstrated in macrocyclic complexes (47) and helicates (48), to our knowledge this is a unique example of the conversion of one metal-organic polyhedron into another via metal exchange.…”
Section: Resultsmentioning
confidence: 87%